Expression of serum HSP27 under exercise-induced muscle damage in elite greco-roman wrestlers - Zurek, P.; Kasperska, A.; Krzysztoszek, M.; Hübner-Wozniak, E.; Zembron-Lacny, A. (Journal of Combat Sports and Martial Arts, 2013)
In response to stress, cells rapidly produce proteins known as heat shock proteins (HSPs) that are considered to be molecular chaperones, playing a universal role in maintaining cellular homeostasis. Among the subset of stress-responsive proteins, evaluation of HSP27 level is considered to be a new approach to monitoring exercise training and adaptive mechanisms. The aim of the study was to assess whether the wrestling training increases production of HSP27 which can stimulate the regeneration of damaged skeletal muscle in athletes. Material and methods. Blood samples were collected from nine elite Greco-Roman wrestlers during the conditioning camp at in-season period (June) including efforts of a comprehensive impact such as running, kayaks, games, strength (50.8%), efforts of the impact of targeted force (15.4%), and special/wrestling training (30.8%). Nine healthy and untrained males made a reference group. Results. It was found that HSP27 concentration was approx. 40% higher in wrestlers than non-athletes and correlated with total plasma creatine kinase (CK) activity (r = -0.734, P<0.05). Wrestlers showed a body mass index (BMI), fat mass (FM) and free fat mass (FFM) on higher level than in non-athletes. BMI, FM and FFM significantly correlated with CK activity. Moreover, CK activity inversely correlated with nitro-oxidative index NO/H 2 O 2 (r = -0.798, P<0.05). Conclusions. In conclusion, muscle damage induced by wrestling training is important factor modulating changes in nitro-oxidative ratio and HSP27 expression as well as body composition. High HSP27 may be implicated in the regenerative process in Greco-Roman wrestlers.